سياسة اليابان الخارجية والأمنية من 2012 إلى 2018 في ظل التأثيرات الإقليمية والدولية - الجميلى، عمر أسامة ياسين (جامعة البعث, 2019)
The Japanese government, led by current Prime Minister Shinzo Abe, has made changes in its domestic policy that Japan has never seen before, where the results reflected directly on its foreign and security policy, while its former policy was characterized by political and military stalemate and focusing only on the economic and technological fields, these changes represented a fundamental turning point in Japan's behavior and external interaction with its regional environment, and gave a clear signal in the formulation of a new policy characterized by normal policy that Japan lacked it because its regional and international isolation policy as a result of its peaceful constitution, These changes at the domestic and external levels are coming as a response to Japan's interests and national security requirements against the regional threats representing by China's military and economic rise. In addition, Japan has strengthened the relationship and security cooperation with the US ally as a result of Chinese threats in East Asia, Southeast Asia, historical and maritime dispute between Japan and China, In addition the missiles threat from North Korea, While these changes in Japanese policy have had a negative impact on Japan's already lopsided relations with China and Korean peninsula, but Japan at the same time Has gained support from other countries fearing Chinese hegemony in the South China Sea.
قامت حكومة اليابان بزعامة رئيس الوزراء الحالي "شينزو آبي" بإجراء تغييرات في سياستها الداخلية لم تشهدها اليابان من قبل، حيث انعكست نتائجها بصورة مباشرة على سياستها الخارجية والأمنية، بعد أن كانت تتسم سياستها سابقا بحالة من الجمود السياسي والعسكري والاهتمام فقط بالمجال الاقتصادي والتكنولوجي، هذه التغييرات مثلت نقطة تحول جوهري في سلوك اليابان وتفاعلها الخارجي مع بيئتها الإقليمية، واعطت إشارة واضحة في رسم سياسة جديدة تتصف بالطبيعية افتقرت لها اليابان بسبب سياسة العزلة الإقليمية والدولية نتيجة دستورها ذو الطابع السلمي، حيث تعتبر هذه التغييرات على المستوى المحلي والخارجي بمثابة استجابة لمصالح اليابان ومتطلبات أمنها القومي ضد التهديدات الإقليمية المتمثلة بصعود الصين العسكري والاقتصادي. بالإضافة إلى ذلك قامت اليابان بتعزيز العلاقة والتعاون الأمني مع الحليف الأمريكي، نتيجة التهديدات الصينية في شرق آسيا وجنوب شرق آسيا والنزاع التاريخي والبحري بين اليابان والصين بالإضافة إلى التهديدات الصاروخية لكوريا الشمالية، في المقابل أثرت هذه التغييرات في السياسة اليابانية تأثيرا سلبيا على علاقات اليابان الفاترة أصلا وغير المستقرة مع الصين وشبه الجزيرة الكورية، لكن اليابان في نفس الوقت كسبت تأييد دول أخرى تخشى الهيمنة الصينية في جنوب البحر الصيني.
Keywords: العلوم السياسية -- العلاقات الدولية -- السياسة الخارجية اليابانية -- السياسة الأمنية اليابانية